2022
DOI: 10.47068/ctns.2022.v11i22.029
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining the Quality of Carnation Cut Flowers Depending on Temperature

Abstract: In the assortment of cut flowers, carnations (Dianthus caryophyllus L.) fall in the first places, with a large number of varieties, of various colors, being appreciated on the cut flowers market. Carnations flowers that cannot be sold immediately after harvest, being a time of year when the market offers an abundance of cut flower species, they are prone to rapid depreciation under normal environmental conditions. Carnation is an important ornamental plant, which is used as a potted plant as well as a cut flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The fruits of Chinese buckthorn (Rhamnus utilis) are considered to have the highest vitamin C content, reaching levels up to 2500 mg/100 g [49]. According to Pop et al (2013) [50], ascorbic acid can be found in many other fruits such as Fragaria x ananassa varying between 13.79 mg/100 g and 44.05 mg/100 g. In addition, vitamin C is an important component of other plant organs as well, such as roots in carrots ranging from 8.51 to 11.91 mg/100 g or tomatoes 19.76 mg/100 mL [51,52]. Regarding color filters, the vitamin C content of red-leaf pak choi significantly accumulated under the influence of blue LED light at 460 nm, compared with supplemental UV-A light at 400 nm and at 380 nm which significantly decreased the vitamin C content.…”
Section: Discussionmentioning
confidence: 99%
“…The fruits of Chinese buckthorn (Rhamnus utilis) are considered to have the highest vitamin C content, reaching levels up to 2500 mg/100 g [49]. According to Pop et al (2013) [50], ascorbic acid can be found in many other fruits such as Fragaria x ananassa varying between 13.79 mg/100 g and 44.05 mg/100 g. In addition, vitamin C is an important component of other plant organs as well, such as roots in carrots ranging from 8.51 to 11.91 mg/100 g or tomatoes 19.76 mg/100 mL [51,52]. Regarding color filters, the vitamin C content of red-leaf pak choi significantly accumulated under the influence of blue LED light at 460 nm, compared with supplemental UV-A light at 400 nm and at 380 nm which significantly decreased the vitamin C content.…”
Section: Discussionmentioning
confidence: 99%